Feeding regime synchronizes circadian clock in choroid plexus - insight into a complex mechanism - Dočkal, Tereza; Houdek, Pavel; Semenovykh, Kateryna; Rangotis, Revan; Sládek, Martin; Sumová, Alena (Cellular and molecular life sciences, 2025)
The circadian clock in choroid plexus (ChP) controls processes involved in its physiological functions, but the signals that synchronize the clock have been sparsely studied. We found that the ChP clock in the fourthventricle (4V) is more robust than that in the lateral ventricle (LV) and investigated whether both clocks use information about mealtime as a signal to synchronize with the current activity state. Exposure of mPer2Luc mice to a 10-day reverse restricted feeding (rRF) protocol, in which food was provided for 6 h during daytime, advanced the phase of the ChP clock in 4V and LV, as evidenced by shifted (1) PER2-driven bioluminescence rhythms of ChP explants ex vivo and (2) daily profiles in clock gene expression in both ChP tissues in vivo. In contrast, clocks in other brain regions (DMH, ARC, LHb) of the same mice did not shift. The 4V ChP responded more strongly than the LV ChP to rRF by modulating the expression of genes to ensure a decrease in resistance to cerebrospinal fluid drainage and increase the secretory capacity of ChP cells. Mechanistically, rRF affects the ChP clock through food-induced increases in insulin, glucose and temperature levels, as in vitro all three signals significantly shifted the clocks in both ChP tissues, similar to rRF. The effect of glucose was partially blocked by OSMI-1, suggesting involvement of O-linked N-acetylglucosamine posttranslational modification. We identified mechanisms that can signal to the brain the time of feeding and the associated activity state via resetting of the ChP clock.
Keywords: Male; Period Circadian Proteins; Temperature; Circadian Clocks; Mice, Inbred C57BL; Animals; stravovací zvyklosti; Feeding Behavior; O-GlcNAc; cirkadiánní proteiny Period; Glucose; cirkadiánní hodiny; Mice, Transgenic; Mice; myši inbrední C57BL; cirkadiánní rytmus; Restricted feeding; mužské pohlaví; Gene Expression Regulation; Circadian clock; Choroid Plexus; ventriculi laterales; Choroid plexus; regulace genové exprese; plexus chorioideus; Insulin; myši transgenní; zvířata; Circadian Rhythm; Lateral Ventricles; myši